An Analysis of Racism in Down Second Avenue (2011) - Khayaidee, Suchinda; Suranakkharin, Todsapon; Chantharothai, Sasitorn (Journal of Community Development Research (Humanities and Social Sciences); Vol 13 No 1 (2020): January - March 2020DO - 10.14456/jcdr-hs.2020.3, 2020)
Racism is one of the continually controversial issues in a society. Its victims suffer because of unequal distribution of resources, inequality in career chances, income, and access to opportunities. Therefore, studying about the effects of racism is the initial step to help readers understand and be more aware of it. This study focuses on the analysis of effects of three forms of racism: institutionalized, internalized, and intra-racial racisms, on the characters in a South African writer’s, Ezekiel Mphahlele’s, novel, Down Second Avenue (2011). This study aims to answer the question how the three forms of racism are reflected within the novel, through the characters and situations, by investigating an autobiographical novel written by a South African citizen who witnessed and experienced a series of racial discrimination himself. The data collection method of this study employs content and descriptive analysis as the instrument. The study applies the qualitative research methods to analyze and discuss the effects of the three forms of racism. The results of the analysis show that characters in the novel are most affected by and suffered from the consequences of institutionalized racism, internalized racism, and intra-racial racism, respectively. The study serves as guidelines in examining forms of racism reflected in other literary works and media contents. Keywords: Forms of Racism, Literary Criticism, Institutionalized Racism, Internalized Racism, Intra-Racial Racism, South Africa